Change Management in the Public Sector - Selvadurai, Amanda (Université d'Ottawa | University of Ottawa, 2013)
This study explored public sector employee perceptions regarding what strategies are required to create change that achieves desired results in public sector organizations. The theoretical framework for this study is the eight step model for transforming organizations recommended by John P. Kotter in 1995. A qualitative research design was employed, involving in-depth interviews with six employees of the Canadian Public Service, to test the alignment of Kotter’s eight step model with the perceptions of public sector employees. The study revealed that three of Kotter’s eight steps were aligned with the perceptions of the public sector employees interviewed. These three steps were forming a powerful guiding coalition, creating a vision, and communicating the vision. Based on this alignment, further recommendations on leadership, senior/middle management, development/communication of a vision, stakeholder involvement and training were made. This study concludes with an identification of proposed future areas for research to complement the findings outlined.